Psychometric evaluation of a newly developed elderly - Constipation Impact Scale - Abdul Wahab, Patimah; Mohd Yusoff, Dariah; Abdul Kadir, Azidah; Ali, Siti Hawa; Lee, Yeong Yeh; Kueh, Yee Cheng (2020)
Background. Chronic constipation is a common symptom among the elderly, and it may affect their quality of life (QoL). A lack of available research focused on the elderly means that this effect is not well understood. This study aimed to develop and validate a new scale (Elderly-Constipation Impact Scale (E-CIS)) to measure the impact of chronic constipation on QoL among the elderly. Methods. A pool of items was generated from a qualitative study, literature reviews, and expert reviews. Exploratory factor analysis (EFA) was performed on the original 40 items of the E-CIS and followed by 27 items for confirmatory factor analysis (CFA). A total of 470 elderly people with chronic constipation were involved. Results. The mean age of the participants was 68.64 ± 6.57. Finally, only 22 items were indicated as appropriately representing the E-CIS, which were grouped into seven subscales: ‘daily activities’, ‘treatment satisfaction’, ‘lack of control of bodily function’, ‘diet restriction’, ‘symptom intensity’, ‘anxiety’ and ‘preventive actions’. The scale was confirmed as valid (root mean square error of approximation (RMSEA) = 0.04, comparative fit index (CFI) = 0.961, Tucker-Lewis index (TLI) = 0.952 and chisquare/degree of freedom (chiSq/df) = 1.44) and reliable (Cronbach’s alpha: 0.66–0.85, composite reliability (CR) = 0.699–0.851) to assess the impact of chronic constipation on the elderly’s QoL. Conclusions. The E-CIS is useful to measure the impact of chronic constipation on the elderly’s QoL. A further test is needed to determine the validity and reliability of this scale in other elderly population.